PEMODELAN LEVEL ENERGI DISKRET PADA SEL SURYA KUANTUM DOT DAN WELL BERBASIS MATERIAL NANOSTRUKTUR - Ngaderman, Hubertus; Srivajawaty, Ego (Sistem Informasi, 2017)
The aim of this research is to finding out modeling nanostructure solar cell SC with count in electron energy level on the conduction band. Divais photovoltaic nano i.e quantum dot QD and quantum well QW performing wide range transition of electron which can be controlled by the distribution range area suitably of the size dimension QD. QD gives ability absorbance of the ligth where created electron hole coupling which located in the dot. Transition electron in the QD be significant exceed thermal energy and cannot inducted by the fonon thermally while transition hole be simply inducted by the phonon acoustik thermal.Method of this research are concept and computation for accounting energy level. The concept which be used is DEK. The thickness well ð¿ð¤ is small enough (10ðð or less), the set of level energy discret will be in the well and have hinges at the effective mass and the well thickness i.e ð¸ð rising with reduction ðâ or ð¿ð¤. Maximum energy ð¸1 = 3,77 Ã 104ðð at the thickness layer ð¿ð¤ = 0,1ðð. Maximum energy ð¸2 = 1,51 Ã 105ðð at the ð¿ð¤ = 0,1ðð. âð¸ is difference magnitude energy in the starting point 0,1ðð i.e 1,13 Ã 105ðð and in the last thickness QW i.e 10ðð is 1,13 Ã 101ðð. Therefore transition electron in the QW be significantly exceed thermal energy and cannot inducted by the phonon thermal.